PENDEKATAN TRANSFORMATIVE LEARNING DALAM PENGEMBANGAN PROFESIONALISME GURU [TRANSFORMATIVE LEARNING APPROACH IN TEACHER PROFESSIONAL DEVELOPMENT] - Sarinah Lo (Polyglot: Jurnal Ilmiah, 2024)
Studies indicate that many teachers who have gone through Teacher Professional Development programs demonstrate no deep change in their educational perspectives and practices. Using a systematic literature review and critical reflection lens, this study aims to provide an alternative for better teacher professional development efficacy. Based on the transformative learning framework, I propose four areas of change that include: the attitude of learning, the approach to learning, the content of learning, and the climate of learning.